Peak height velocity and muscle mass in young soccer players - Hernández Camacho, J. D.; Huelva Leal, A. B.; Martinez-Sanz, J. M.; Lahoz Ruano, M. D.; Vázquez Carrión, J. (Revista Española de Nutrición Humana y Dietética, 2018)
Introduction: It has been reported that peak height velocity could be an important period in body development in athletes. The objective was to examine the peak height velocity and maturity offset in young soccer players and analyze anthropometrical measures relate with body development. Material and Methods: Fifty-eight male young soccer players were studied. They were categorized in three diverse age categories, Under-19 (post-peak height velocity), Under-16 (on peak height velocity) and Under-14 (pre-peak height velocity) years old. Height, sitting height, weight, girths and skinfolds were measured to determine peak height velocity, maturity offset and body components. Descriptive statistics means (Standard Deviation) were calculated. One-way ANOVA analyses and Pearson correlations were determined. The level of significance was set at p<0.05. Results: The mean height and weight values were 167.63 (10.52) cm and 60.12 (12.43) kg, the medium fat mass was 13.49 (3.65)%. The average muscular transverse areas for arm, thigh and calf were 41.70 (10.82) cm2, 154.87 (38.02) cm2 and 85.76 (17.67) cm2 respectably. The average PHV was 13.97 (0.53) years and the median maturity offset was 1.00 (1.92) years. Significant differences were found among the three age categories analyzed for the anthropometrical elements and for the maturity offset. Significant correlations between maturity offset and anthropometrical components were obtained. Conclusions: In agreement with previous studies, increases on anthropometrical components and muscle areas were reported after the peak velocity. Consequently, peak height velocity and maturity offset should be considered in young soccer players` management.